(untitled) (Bangladesh Journal of Botany, 2025)
This study assessed the impact of over eight years of continuous cultivation of transgenic Bt cotton on the soil ecological environment by examining rhizosphere and non-rhizosphere soils from five regions in southern Shanxi, China. Changes in enzyme activities, Bt protein residues, and physicochemical characteristics of soils in the rhizosphere and non-rhizosphere environment during the harvest period were investigated. Results showed that rhizosphere soil had significantly higher organic matter and water content, but significantly lower alkali-hydrolyzable nitrogen, available phosphorus, and available potassium. Rhizosphere soil contained more Bt protein residues with regional variations. Enzyme activities differed significantly; rhizosphere soil had higher polyphenol oxidase, alkaline phosphatase, sucrase, and peroxidase activities, but lower urease. Correlation analysis revealed relationships between soil physicochemical properties, Bt protein content, and soil enzyme activities. Principal component analysis identified soil available potassium and urease activity as key factors influencing the rhizosphere environment. These findings highlight the needs for long-term monitoring to support rational cultivation practices and ecological safety assessment of Bt crops. Bangladesh J. Bot. 54(4): 927-934, 2025 (December)